1985
DOI: 10.1161/01.cir.71.4.745
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive pulsed Doppler echocardiographic detection of the direction of shunt flow in patients with atrial septal defect: usefulness of the right parasternal approach.

Abstract: Noninvasive pulsed Doppler echocardiography combined with two-dimensional echocardiography by the right parasternal approach was performed to detect the shunt flow through the defect in 31 patients with suspected secundum atrial septal defect (ASD). A defect of the interatrial septum was seen on the two-dimensional echocardiograms of 30 of 31 patients. In all the 30 patients, Doppler signals of shunt flow could be recorded by placing the sample volume in the center of the defect on the two-dimensional echocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…2C) that could be caused by a reversal of the left-to-right shunting. This has been observed in humans with right ventricle failure or stiffness in which the left-to-right shunting decreases and right-to-left shunting may occur and increase the flow in the left atrium, causing the increase in MV flow (31,32). Other causes explaining the increased MV pressure gradient were eliminated.…”
Section: Resultsmentioning
confidence: 92%
“…2C) that could be caused by a reversal of the left-to-right shunting. This has been observed in humans with right ventricle failure or stiffness in which the left-to-right shunting decreases and right-to-left shunting may occur and increase the flow in the left atrium, causing the increase in MV flow (31,32). Other causes explaining the increased MV pressure gradient were eliminated.…”
Section: Resultsmentioning
confidence: 92%
“…Minagoe and colleagues demonstrated that the right parasternal view provided a useful window to assess the direction of flow across an atrial septal defect many years ago, 6 and later that this approach provided visualization of the deviated interatrial septum in patients with mitral stenosis and giant left atria. 7 In this second study, the right parasternal view was also used to assess flow velocity within the IVC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a study similar to OUTS, pulsed Doppler echo combined with 2D echo was reported to be a useful tool for detecting bidirectional flow patterns in patients with atrial septal defect (Minagoe et al, 1985).…”
Section: Discussionmentioning
confidence: 99%